2022
DOI: 10.1021/acs.inorgchem.2c00212
|View full text |Cite
|
Sign up to set email alerts
|

Cerocene and Lanthanocene Chalcogenides: Synthesis, Structure, and Luminescence

Abstract: A series of lanthanide chalcogenides {[η5–1,3-(Me3C)2C5H3]2Ln}2(μ-η2:η2-Te2) (Ln = Ce 1, La 2), {[η5–1,3-(Me3C)2C5H3]2Ln­(THF)}2(μ-Se) (Ln = Ce 3, La 4), and {[η5–1,3-(Me3C)2C5H3]2Ln­(THF)}2(μ-Te) (Ln = Ce 5, La 6) can be readily obtained by the reaction of the alkyl complexes [η5–1,3-(Me3C)2C5H3]2Ln­(CH2C6H4-o-NMe2) with elemental selenium or tellurium in the presence of 9-borabicyclo[3.3.1]­nonane (9-BBN). The reaction of the alkyl complexes [η5–1,3-(Me3C)2C5H3]2Ln­(CH2C6H4-o-NMe2) with 9-BBN in 1:2 molar ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…[ 7,8 ] Since dynamic PL properties are associated with trap filling in the electronic transition levels, rich and tunable defects are urgent for dynamic PL implementation. [ 7–11 ] Currently, only a few dynamic PL materials have been reported in several inorganic persistent phosphors. Therefore, it remains a challenge to explore novel strategies and new systems to construct diverse and color controllable dynamic PL in versatile systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 7,8 ] Since dynamic PL properties are associated with trap filling in the electronic transition levels, rich and tunable defects are urgent for dynamic PL implementation. [ 7–11 ] Currently, only a few dynamic PL materials have been reported in several inorganic persistent phosphors. Therefore, it remains a challenge to explore novel strategies and new systems to construct diverse and color controllable dynamic PL in versatile systems.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the construction of non‐charge transfer type epitaxial layers are an ideal choice for ensuring stable luminescence of perovskite and holding promise to achieve dynamic PL. [ 33 ] Notably, the spinel MgGa 2 O 4 crystal exhibits blue luminescence originating from the self‐activation of octahedral GaO 6 , [ 11 ] in which the strong binding energy between photogenerated electron (Ga 3+ ) and hole (O 2− ), defined as Frenkel excitons, is expected to prevent the interface charge–transfer, making it a promising epitaxial layer to realize anti‐fluorescence quenching. To date, there is still no report of dynamic PL modulated by engineering defect tolerance in halide perovskite heterostructure.…”
Section: Introductionmentioning
confidence: 99%
“…15 a It is worth mentioning that the benzamidinate ligands used in this work possess SiMe 3 groups which have been proved to be useful in stabilizing Ln( ii ) complexes. 18 Although similar dinuclear linkages were reported in other lanthanide compounds, 1 a , e ,3,4,19 only a handful of them have been synthesized via divalent lanthanide complexes, 1 e ,3–4,19 g , n and ytterbium analogues are very scarce. 20 The magnetic properties of these compounds were studied as well which revealed that 3 represents a rare example of lanthanide telluride SMMs.…”
mentioning
confidence: 69%